The federal government and Canada's COVID-19 responses: from 'we're ready, we're prepared' to 'fires are burning'. Issue 1 (22nd January 2022) - Allin, Sara; Fitzpatrick, Tiffany; Marchildon, Gregory P.; Quesnel-Vallée, Amélie
Abstract: Canada's experience with the coronavirus disease-2019 (COVID-19) pandemic has been characterized by considerable regional variation, as would be expected in a highly decentralized federation. Yet, the country has been beset by challenges, similar to many of those documented in the severe acute respiratory syndrome outbreak of 2003. Despite a high degree of pandemic preparedness, the relative success with flattening the curve during the first wave of the pandemic was not matched in much of Canada during the second wave. This paper critically reviews Canada's response to the COVID-19 pandemic with a focus on the role of the federal government in this public health emergency, considering areas within its jurisdiction (international borders), areas where an increased federal role may be warranted (long-term care), as well as its technical role in terms of generating evidence and supporting public health surveillance, and its convening role to support collaboration across the country. This accounting of the first 12 months of the pandemic highlights opportunities for a strengthened federal role in the short term, and some important lessons to be applied in preparing for future pandemics.